Associations between perceived social and physical environmental variables and physical activity and screen time among adolescents in four European countries - Bucksch, J; Kopcakova, J; Inchley, J; Troped, P J; Sudeck, G; Sigmundova, D; Nalecz, H; Borraccino, A; Salonna, F; Dankulincova Veselska, Z; Hamrik, Z (International journal of public health, 2019)
OBJECTIVES: Associations between the perceived social and physical environment and self-reported moderate-to-vigorous physical activity (MVPA) and screen time (ST) were examined among adolescents in four European countries. METHODS: Representative samples were surveyed with standardised methodologies. Associations between environmental variables and meeting MVPA recommendations and tertiles of ST were tested in gender-specific logistic regression models. Moderation by country and country-specific relationships were also examined. RESULTS: The most consistent findings across countries were found for the significant associations between neighbourhood social environment and MVPA in both boys and girls. Significant associations with the physical environment varied more between countries and by gender. The most consistent negative associations with ST were found for the social environmental variable of having parental rules for spending time outside the home. CONCLUSIONS: The present findings provided evidence for the generalisability of the associations between environmental correlates and MVPA across four European countries. The findings show clear differences in correlates for MVPA and ST. Further research is needed to better understand the unique aspects of the social and physical environment which explain each of the two behaviours.
Keywords: Adolescent; sociální prostředí; Europe; Self Report; Social and physical environment; Male; životní prostředí; čas strávený před obrazovkou; charakteristiky bydlení; Social Environment; lidé; Humans; Child; European countries; sexuální faktory; Age Factors; Evropa; Residence Characteristics; Sex Factors; věkové faktory; Environment; zpráva o sobě; cvičení; průřezové studie; mužské pohlaví; dítě; Cross-Sectional Studies; ženské pohlaví; mladiství; Exercise; Female; Screen time; Physical activity; Screen Time; Health Behaviour in School-aged Children (HBSC) study